1, 3‐Dipolar Cycloaddition of Benzofuranone Derivatives and Azomethine Ylides Promoted by Simple Functional Ionic Liquids: Direct Access to Highly Substituted Pyrrolidine and Spirocyclic Benzofuranone. Issue 15 (16th September 2016) - Zhang, Chuan‐Bao; Dou, Pei‐Hao; Zhang, Jun; Wei, Qiang‐Qiang; Wang, Yan‐Bo; Zhu, Jun‐Yan; Fu, Ji‐Ya; Ding, Tao
Abstract: We have successfully established an efficient catalytic system, which was effective for construction of both spiro[pyrrolidine‐benzofuran‐3‐one] and spiro[pyrrolidine‐benzofuran‐2‐one] compounds. The first 1, 3‐dipolar cycloaddition of 2‐alkylidene‐benzofuran‐3‐one with azomethine ylides with simple functional ionic liquids as catalysts was developed, affording a variety of spiro[pyrrolidine‐benzofuran‐3‐one] compounds containing highly substituted pyrrolidine motifs with a spiro quaternary stereogenic center in excellent yields (73‐99 %). The highly efficient catalytic system exhibited broad substrate scopes under mild conditions. Meanwhile, this catalytic system was also extended to the cycloaddition of 3‐alkylidene‐benzofuran‐2‐one with azomethine ylides and gave spiro[pyrrolidine‐benzofuran‐2‐one] compounds in high yields (82‐99 %) and 1, 3‐dipolar cycloaddition of 2‐alkylidene‐benzofuran‐3‐one with pyrazolidinone‐based dipoles giving the desired products in 25–85 % yields. Abstract : The first 1, 3‐dipolar cycloaddition of 2‐alkylidene‐benzofuran‐3‐one with azomethine ylides was developed to construct a variety of spiro[pyrrolidine‐benzofuran‐3‐one] compounds containing spiro quaternary stereogenic centers and highly substituted pyrrolidines efficiently, affording the corresponding compounds in excellent yields (up to 99 %). The highly efficient catalytic system exhibited high reactivity, and broad substrate scopes. When the catalyst was recycled and reused five runs, the high yield was still obtained (90 %).